A new polyembryonic species of Eriotheca (Malvaceae, Bombacoideae) from the Brazilian Cerrado - Yoshikawa, Vania N.; Marinho, Rafaela C.; Mendes-Rodrigues, Clesnan; Oliveira, Paulo E. A. M.; Duarte, Marília C. (Phytotaxa, 2024)
We describe a new species endemic to the Cerrado province from the state of Minas Gerais: Eriotheca luzensis (Malvaceae, Bombacoideae). This new species can be identified by its yellow pubescent indumentum associated with ferruginous scales, mainly grouped in the calyx apex. We provide a diagnosis, complete description, taxonomic comments, a key to differentiate E. luzensis from its congeners from the state of Minas Gerais, a plate with diagnostic features, a distribution map, and a preliminary conservation status. We also included notes on the reproductive system with information on the occurrence of polyembryony in the new species.